Digital signal processing 101 everything you need to know to get started - Parker, Michael 1963- (Cambridge, MA Newnes, 2017)
Digital Signal Processing 101: Everything You Need to Know to Get Started provides a basic tutorial on digital signal processing (DSP). Beginning with discussions of numerical representation and complex numbers and exponentials, it goes on to explain difficult concepts such as sampling, aliasing, imaginary numbers, and frequency response. It does so using easy-to-understand examples with minimum mathematics. In addition, there is an overview of the DSP functions and implementation used in several DSP-intensive fields or applications, from error correction to CDMA mobile communication to airborne radar systems.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Signal processing -- Digital techniques; Electronic books